Challenges and outcomes of airway surgery in a post‐war low‐resource setting: A case series from Mekelle, Ethiopia - Daniel G. Eyassu; Estephania Candelo; Brhanu H. Asgedom; Katherine P. Wallerius; Shaina W. Twardus; Weston L. Niermeyer; Katerina J. Green; Tejas S. Athni; Joshua P. Wiedermann (Laryngoscope Investigative Otolaryngology)
Abstract Objective This study aims to document and analyze the challenges and outcomes of performing complex airway surgery in a low‐resource, post‐war setting in Mekelle, Ethiopia. Methods This prospective case series examines clinical data from five patients who underwent airway reconstruction surgeries and one patient who underwent total laryngectomy at Ayder Comprehensive Specialized Hospital in Mekelle. Data included patient demographics, airway stenosis etiology and severity, operative details, postoperative outcomes, complications, and hospital length of stay. Ethical approval was obtained from institutional review boards at Mayo Clinic and Mekelle University. Results The study included six patients aged 9–62 years, with surgeries comprising three cricotracheal resections, two tracheal resections, and one laryngectomy. Three reconstructions were for war‐related injuries. Challenges included power outages during surgeries, limitations in medical supplies and equipment, and inadequate perioperative care. Despite these, three patients requiring tracheostomies were successfully decannulated within a year. However, complications such as restenosis, infections, and the need for reintubation were common. Conclusion Airway surgeries in a low‐resource, post‐war setting face significant hurdles, including perioperative care quality, resource limitations, and infrastructure issues. Successful outcomes require multidisciplinary training tailored to local contexts, investments in hospital infrastructure and reliable electricity, and proper perioperative nutrition. This study highlights the need for comprehensive interventions to improve surgical care in such settings. Level of evidence: IV.